Roundtable synthesis: setting a demand-driven research agenda for advancing Anticipatory Action and addressing Fragility, Conflict, and Migration dynamics - Nohayi, Ngowenani; Sanchez Ramirez, Juan Carlos; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2023)
In fragile and conflict-affected settings and host communities, hunger, severe malnutrition, and water insecurity are on the rise, directly impacting the resilience of food, land and water systems. The interplay of these issues often gives rise to conflict and forced migration, with women and other marginalized groups disproportionately affected due to their limited access to channels of power and influence during shocks and crises. In these fragile contexts, the agri-food system is central to food security, livelihoods, and sustainable development. These systems are often characterized by instability, restricted access to resources and gender inequalities. While these challenges are extensive, their causes, manifestations and impacts can vary widely. To address these compounding challenges, government, humanitarian and development organizations need evidence to inform collective efforts. The concept of anticipatory action has emerged as a proactive approach to mitigate disasters and crises. Anticipatory Action involves a series of measures strategically implemented to prevent or mitigate potential disaster impacts before a shock occurs or before acute impacts are felt. This document compiles stakeholders' expressed needs for CGIAR research. It presents insights from a roundtable discussion at the Global Dialogue Platform on setting a research agenda that guides good practices for anticipatory action initiatives in fragile and conflict-affected settings. This discussion was part of an ongoing series of learning and exchange events coordinated through Work Package 1 (WP1) of the Fragility, Conflict and Migration Initiative to promote an anticipatory action-community of practice led by the International Water Management Institute. Continuous engagements with diverse organizations are essential for shaping a demand-driven research strategy. This report, therefore, lays the foundation for an ongoing commitment to continued collaboration; it summarizes the strategic importance of demand-driven research in addressing the complex challenges of Anticipatory Action and dynamics of fragility, conflict and migration. The roundtable stressed the significance of advancing research, policy, and practice in strengthening anticipatory action and conflict resilience. It emphasized the importance of evidencebased approaches, highlighting the need for tailored strategies in addressing the unique dynamics of anticipatory action and fragility, conflict and migration issues. Interdisciplinary analyses were deemed crucial to addressing the interconnectedness of climate, conflict, displacement and political dynamics. Recommendations include integrating social, political and cultural dimensions into research methodologies while respecting local dynamics without compromising neutrality.